Questioning technique to heighten speaking skills among students in third year of intensive high school “b” at unidad educativa del milenio Bernardo Valdivieso in the city of Loja during the 2018-2019 academic year - Zapata Vicente, Maritza Ines (2019)
The general objective of this research was to apply the questioning technique to heighten speaking skills among students in third year of intensive high school “B” at Unidad Educativa del Milenio Bernardo Valdivieso in the city of Loja during the 2018-2019 academic year. The scientific, descriptive, statistical, and analytic/synthetic methods were applied to collect data, describe, analyse, and present the findings of the research. Tests and questionnaires were applied to twenty-four students at the beginning of the intervention plan to identify their speaking limitations and at the end to evaluate their progress; observation sheets and field notes were also used to document the classroom events. The results showed that the questioning technique generated a satisfactory increase in students’ speaking skills. In conclusion, this technique encouraged and challenged learners to use English in the classroom while actively participating in the lesson.